Comunicação e liderança : em busca da dimensão sensível - Christofoli, Márcia Pillon (2020)
COMMUNICATION AND LEADERSHIP: IN SEARCH OF THE SENSITIVE DIMENSION This research focuses on the study of leadership and communication, and proposes to: a) Discuss how communication processes contribute [can contribute] to the human and sensitive dimension of leadership; b) Highlight the possible relationships between the communication, culture and leadership processes; and c) Discuss the role and skills of leaders in communication processes. Using the Depth Hermeneutics (THOMPSON, 2009) method, this research, of an exploratory nature, was developed through bibliographic search (GIL, 2008) and field research, with in-depth interviews (DUARTE, 2006) with leaders who work with change and who are part of the Alliance for Innovation (Aliança para Inovação), in the city of Porto Alegre/RS. We set from the notion that leadership is a communicative act, in which a subject influences others, in the search for organizational goals and objectives, considering that the organizational context develops today from continuous processes of change. The organization, in this research, is approached from of its human dimension (built and reconstructed from/by relationship and communication), and from its permanent state of change and transformation, in the search for results that set it apart in the market. In this sense, relationship and communication tend to be the essence of change under the responsibility of the leader. The analysis of the interviews revealed, however, that an instrumental view of communication still prevails, which constitutes a paradox in times of innovation and organizational change. We understand that there is a need to (re)visit the concepts of quantum organizations, using other approaches such as Teal organizations (LALOUX, 2017), making it possible to think of a leadership directed towards the other and fundamentally considering the sensitive [and human] dimension of communication, based on relationship, bonding and dialogue.